The axial fan design and commissioning test with nonuniform inlet flow. Issue 1 (1st June 2022) - Qu, Xiaoli; Ren, Zebin; Yang, Wenguo; Luo, Yuanqiang
Abstract: According to the two-dimensional flow theory of the axial fan rotor blades and the aerodynamic characteristics of the low speed wind tunnel, combined with the fan aerodynamic efficiency and wind tunnel pressure loss coefficient, a new equation which points out the inherent relationship of the fan blade setting angle, fan rotating speed and flow rate in wind tunnel circuit is derived. So a new method for fan rotor blade setting angle adjustment to satisfy the fan performance at off-design point by getting the test results of fan operating parameters but without the fan total pressure rise in the low speed wind tunnel is developed. Following the new method, the fan rotor blade setting angle adjusting value was provided directly only with the fan rotating speed and flow velocity in the wind tunnel test section, the adjusting target was achieved successfully by the new blade setting angle, the cost of the wind tunnel commissioning test were saved. The test results show that, after increasing the fan rotor blade setting angle by 4.5 degrees, when the flow velocity in the wind tunnel test section reaches 60m/s, the fan rotating speed is 570rpm, the deviation from the predicted fan rotating speed value of 575rpm is 0.9%. For the same test section flow velocity, the predicted value and the real value of the fan rotating speed are in good agreement, it proves that this method is reliable and accurate in practical application.